2003
DOI: 10.1046/j.1442-9071.2003.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial status in the subtypes of primary angle closure glaucoma

Abstract: There is a significant decrease in the corneal endothelial cell density in eyes that have had an acute attack of angle closure glaucoma and in eyes with chronic PACG. The endothelial cell population in eyes with sub-acute PACG and in the fellow eyes of all subtypes of PACG is not significantly different from the normal population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 6 publications
2
57
1
4
Order By: Relevance
“…In our study, we found a mean endothelial cell loss of approximatively 8% for the central and peripheral cornea during a 6-month period after surgery, which is higher than the reported age-related endothelial cell loss, 15 but comparable or even less to that following cataract extraction 16,17 or other glaucoma filtering procedures. 6,7,18 Smith et al 6 calculated a mean central endothelial cell loss ranging from 1.6 to 54.8% three months after glaucoma surgery, correlated with postoperative AC depth and intraoperative corneal touch. Fiore et al 7 reported a 12.4% and a 11.6% reduction in peripheral and central endothelial cell counts after 4-6 months of filtration surgery in eyes with shallow AC and iridocorneal touch.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found a mean endothelial cell loss of approximatively 8% for the central and peripheral cornea during a 6-month period after surgery, which is higher than the reported age-related endothelial cell loss, 15 but comparable or even less to that following cataract extraction 16,17 or other glaucoma filtering procedures. 6,7,18 Smith et al 6 calculated a mean central endothelial cell loss ranging from 1.6 to 54.8% three months after glaucoma surgery, correlated with postoperative AC depth and intraoperative corneal touch. Fiore et al 7 reported a 12.4% and a 11.6% reduction in peripheral and central endothelial cell counts after 4-6 months of filtration surgery in eyes with shallow AC and iridocorneal touch.…”
Section: Discussionmentioning
confidence: 99%
“…Key corneal endothelial morphology parameters include the endothelial cell density (ECD), and the coefficient of variation of cell area (CV/polymegathism). Both of these measures can be affected by a broad range of disorders, such as contact lens complications [7,8], glaucoma [9,10], dry eye [11], and diabetes mellitus [12,13]. Furthermore, it is predictable that a normal healthy endothelium will have low CV values [14].…”
Section: Introductionmentioning
confidence: 99%
“…(2) A redução da DCEC também é observada em pacientes que apresentam crise aguda de glaucoma primário de ângulo fechado e em pacientes com glaucoma crônico de ângulo estreito; entretanto, a população de células endoteliais em olhos de pacientes com crises subagudas de glaucoma de ângulo estreito, e nos olhos contralaterais de pacientes com glaucoma primário de ângulo fechado não é significativamente diferente da média encontrada em pessoas normais. (3) Alguns autores acreditam que pacientes glaucomatosos têm menor DCEC e que esta redução varia com o tipo de glaucoma. (4) Além disso, a diminuição da DCEC está relacionada com o tempo de permanência da pressão intra-ocular (Po) elevada, sendo aquela maior quanto maior o tempo da persistência da elevação da Po.…”
Section: Introductionunclassified
“…(6)(7)(8) Alguns estudos ao avaliarem a espessura corneana central (ECC), concluíram que esta é significativamente maior em pacientes com crise aguda de glaucoma de ângulo fechado, o que não ocorre nos demais subtipos de glaucoma de ângulo fechado. (3) Outros estudos observaram que a ECC é maior em pacientes hipertensos oculares. (5) O presente estudo foi proposto com o intuito de analisar questões críticas relacionadas ao uso da MMC per-operatória nas trabeculectomias: acometimento da DCEC e variações da ECC no período de seis meses de pós-operatório.…”
Section: Introductionunclassified